“The Distribution of the Lexical Component in ELT Coursebooks and its Suitability for Vocabulary Acquisition from a Cognitive Perspective. A Case Study - Criado, Raquel (International Journal of English Studies, 2009)
The psycholinguistic and neurolinguistic perspective of language acquisition requires some essential conditions in vocabulary acquisition: a) repetitive practice, which allows for data to reach long-term memory, and thus become proceduralised and automatised; b) how relevant the lexical items are regarding the communicative needs of the learners insofar as communicative relevance is linked to frequency in general linguistic usage; c) the potential in vocabulary acquisition, which will necessarily relate to the amount of new lexical items introduced in each one of the units in textbook; d) the way words are taught, i.e. whether aimed at explicit or incidental learning. In order to analyse and evaluate these issues, we will study the lexical items presented in a specific textbook from the point of view of frequency, distribution along the manual, opportunities for rehearsal and repetition (which will depend on frequency), and the nature of the activities centred on vocabulary. The results of this case study will allow us to check whether or not they may stand a comparison against the findings of psycholinguistic and neurolinguistic research on vocabulary acquisition.